A diagnosis of pulmonary tuberculosis and drug resistance among inmates in Mato Grosso do Sul, Brazil - Eunice Atsuko Totumi Cunha; Marli Marques; Maria do Socorro Nantua Evangelista; Maurício Antonio Pompilio; Renata Terumi Shiguematsu Yassuda; Albert Schiaveto de Souza (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: High endemic levels of pulmonary tuberculosis in prisons result from overcrowding, limited access to healthcare, delayed diagnosis, sustained transmission owing to poor control measures, and multidrug resistance. This study evaluated locally implemented measures for early pulmonary tuberculosis diagnosis and evaluated resistance to anti-tuberculosis drugs. METHODS: This transversal study employed data from the Mato Grosso do Sul State Tuberculosis Control Program obtained from 35 correctional facilities in 16 counties for 2 periods (2007-2010 and 2011-2014). RESULTS: Statewide prevalence (per 100,000) was 480.0 in 2007 and 972.9 in 2014. The following indicators showed improvement: alcohol-acid-fast bacillus testing (from 82.7% to 92.9%); cultures performed (55.0% to 81.8%); drug susceptibility testing of positive cultures (71.6% to 62.4%); and overall drug susceptibility testing coverage (36.6% to 47.4%). Primary and acquired resistance rates for 2007-2014 were 21.1% and 30.0%, respectively. Primary and acquired multidrug resistance rates were 0.3% and 1.3%, respectively. CONCLUSIONS: Prevalence rates increased, and laboratory indicators improved as a result of capacity building and coordination of technical teams and other individuals providing healthcare to inmates. Resistance rates were high, thereby negatively affecting disease control.